MENINGKATKAN KESADARAN TENTANG PENTINGNYA MEMBELI PRODUK LOKAL MELALUI KAMPANYE PEMASARAN BAGI SISWA DAN SISWI MA AL-ULYA AL MUBAROK - Hasanah, Tantri; Fahleji, Maulana; Fachrudin, Aris; Rahmatuloh, Riki; Muhidin, Muhidin; Maulana, Maulana; Susanto, Denies; Permadi, Bambang (Gapenas Publisher, 2025)
This research aims to increase the awareness of MA Al-Ulya Al Mubarok students about the importance of buying local products through effective marketing campaigns. This campaign is designed to instill the value of love and pride for domestic products from an early age, in line with the government's efforts and vocational education in supporting the development of local products. The methods used include education, socialization, and the implementation of digital marketing strategies that are in accordance with the characteristics of the millennial generation. The expected result is increased interest and participation of students in buying and promoting local products, so that it can support local economic growth and strengthen.